Carbapenem-Resistant Enterobacteriaceae-Implications for Treating Acute Leukemias, a Subgroup of Hematological Malignancies - Kristin Ølfarnes Storhaug; Dag Harald Skutlaberg; Bent Are Hansen; Håkon Reikvam; Øystein Wendelbo (MDPI AG, 2021)
Acute leukemias (AL) are a group of aggressive malignant diseases associated with a high degree of morbidity and mortality. Patients with AL are highly susceptible to infectious diseases due to the disease itself, factors attributed to treatment, and specific individual risk factors. Enterobacteriaceae presence (e.g., Klebsiella pneumonia and Escherichia coli) is a frequent cause of bloodstream infections in AL patients. Carbapenem-resistant Enterobacteriaceae (CRE) is an emerging health problem worldwide; however, the incidence of CRE varies greatly between different regions. Carbapenem resistance in Enterobacteriaceae is caused by different mechanisms, and CRE may display various resistance profiles. Bacterial co-expression of genes conferring resistance to both broad-spectrum β-lactam antibiotics (including carbapenems) and other classes of antibiotics may give rise to multidrug-resistant organisms (MDROs). The spread of CRE represents a major treatment challenge for clinicians due to lack of randomized clinical trials (RCTs), a limited number of antibiotics available, and the side-effects associated with them. Most research concerning CRE infections in AL patients are limited to case reports and retrospective reviews. Current research recommends treatment with older antibiotics, such as polymyxins, fosfomycin, older aminoglycosides, and in some cases carbapenems. To prevent the spread of resistant microbes, it is of pivotal interest to implement antibiotic stewardship to reduce broad-spectrum antibiotic treatment, but without giving too narrow a treatment to neutropenic infected patients.